Geometallurgy applied to cyanide gold tailings in the Arequipa region and its subsequent processing by Gravimetry - Escalante Escalante, Joselyne Bridgette (2023)
The sample of tailings evaluated in this study belongs to a concentrator plant in the Arequipa region, which has a capacity of 430 TMD, which processes gold ore from artisanal mining. The benefit of these types of minerals is carried out through the cyanidation process, coal in pulp, desorption and refinery. The objective of the research is to evaluate the technical viability of the application of a centrifugal-gravimetric concentrator called Falcon C, whose purpose is to concentrate the gold that was not recovered in the previous stages and in this way take advantage of the metallic values found in said tailings. The reflected light optical microscopy study of the sample determined the presence of minerals such as chalcopyrite, type I sphalerite, galena, pyrite, pyrrhotite, arsenopyrite, hematite and gangues, a scanning electron microscopy study was also carried out, it has been possible to determine that the gold is occluded in the pyrite. Based on the mineralogical studies, centrifugal-gravimetric concentration tests were carried out in Falcon C equipment, whose best test supported a recovery of 60.00% gold and 20.92% silver with a quality of 3.96% gold and 11.46% silver.